حكم الضمان على قتل البهائم المحترمة إذا صالت على الإنسان (دراسة في ضوء القاعدة الاضطرار لا يبطل حق الغير): The Ruling on Compensating for the Killing of Respected Animals if They Attack a Human (The Principle of Necessity does Not Nullify the Right of Others) - Rosmita Rosmita; Rahmayani Rahmayani; Miftahul Jannah (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2026)
This research, which I present to the esteemed reader, discusses the ruling on the liability for killing respected animals if they attack a human (the principle that necessity does not negate the right of others). The aim of the research is to understand the ruling on killing someone else's livestock and the ruling on compensation for killing respected livestock if they attack a person (the principle that necessity does not negate the right of others). The research problem lies in two points: the first, what is the ruling on killing someone else's livestock. Second, what is the ruling on compensating for the killing of respected animals if they attack a human (the principle that necessity does not negate the right of others)? The scientific methodology followed by this research in achieving its objectives is as follows: the inductive method and the deductive method. The most important findings of this research are: First, it is not permissible to intentionally kill someone else's livestock except in cases of necessity, which is when the respected livestock attacks a human. Secondly, there is no liability for the damage in this case, meaning if the animal attacked him, and the principle that necessity does not nullify the right of others was not applied in this case, as it is an exception to the rule.